Maternal feeding practice and nutritional status in stunted children - Apriyani Puji Hastuti; Tintin Sukartini; Yuni Sufyanti Arief; Nursalam Nursalam; Ratna Roesardhyati; Ardhiles Wahyu Kurniawan; Syaifurrahman Hidayat; Elyk Dwi Mumpuningtias; Domingos Soares (Pediomaternal Nursing Journal, 2026)
Introduction: The ability of mothers to supply adequate nutrition is closely linked to the nutritional support given to children aged 6-24 months who experience stunted growth. A mother's responsibilities can be fulfilled through her skills, confidence, and ability to perform tasks and ensure proper nutrition for children aged 6-24 months who are experiencing stunted growth. The objective of this research was to explore the connection between how mothers feed their children and the nutritional health of kids aged 6 to 24 months.Methods: This study employed a cross-sectional correlation analysis utilizing height-for-age z-score tables from the World Health Organization alongside the Infant and Young Children Feeding Practice and Structure Questionnaire. A total of 76 participants were chosen through a cluster random sampling method from five district health centers in Malang Regency. The data were analyzed using the Spearman rank test.Results: The findings indicated a significant association between the mother's capability to meet the nutritional needs of children aged 6-24 months who are stunted (including breastfeeding, food preparation and processing, complementary feeding, responsive feeding, and adherence to stunted therapy) and their nutritional status (measured by upper arm circumference and minimal weight gain), with a p-value of less than 0.05. Additionally, the mothers were responsible for implementing feeding practices.Conclusion: Maternal feeding practices are linked to the nutritional status of children aged 6–24 months who are stunted. This connection is evident in aspects such as breastfeeding, food preparation and processing, complementary feeding, responsive feeding, and adherence to stunting therapy, which relate to nutritional indicators like minimal weight gain and upper arm circumference. However, other indicators did not show a correlation between breastfeeding, food preparation and processing, responsive feeding, and adherence to the nutritional status of stunted children, specifically regarding upper arm circumference.Keywords: feeding practice; maternal; nutritional status; stunted